Impacts of School Entry Age on Academic Growth through 2nd Grade: A Multi-State Regression Discontinuity Analysis. Issue 3 (3rd July 2021) - Johnson, Angela; Kuhfeld, Megan
Abstract: The belief that additional time allows children to become more ready for school has affected public policy and individual practices. Prior studies estimated either associations between school entry age and academic growth or causal effects on achievement measured at one or two points. This article contributes novel causal evidence for the impacts of kindergarten entry age on academic growth in the first three years of school. We embed regression discontinuity into a piecewise multilevel growth model and apply it to rich assessment data from three states. Being a year older leads to higher initial achievement and higher kindergarten growth rates but lower growth rates during 1st and 2nd grades. Effects do not differ by gender or race.